Characterization of the profile and remuneration of business and management peer reviewers accredited by Minciencias, Colombia - Cruz Páez, Fabio Orlando; Parra Montenegro, Lizeth Valeria; Lechuga Cardozo, Jorge Isaac (Universidad de Santander (Colombia), 2021)
Abstract— The purpose of the article is to characterize the profile of peer evaluators in the business and management field accredited by the Ministry of Science, Technology, and Innovation (Minciencias), Colombia, and their opinion about the remuneration for the publication of articles, topics of interest and indented scientific journal categories. The methodology used was quantitative, non-experimental design, and descriptive level. A 15-item questionnaire was used for a random sample of 190 evaluator-investigator pairs. It was found that most business and management researchers are junior category and prefer to find out about the calls through social networks for researchers. They also receive economic benefits from their institutions for publication in primarily high-impact indexed journals such as those indexed to Scopus, with general administration as the preferred topic. It is concluded that the Colombian national research system has great challenges in stimulating the researcher performance within higher education institutions and developing more qualified human talent. In order to respond to the quality system of indexed journals, training efforts and retention and development programs must be implemented for researchers who act as peer reviewers in scientific journals.